Application of packaging technology to improve the quality of strawberry milk in Tulungrejo Village, Batu. - Sugiarto, Yusron (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2023)
This program targets unproductive Micro, Small and Medium-sized Enterprises (MSMEs) farmer groups in Dusun Wonorejo, Desa Tulungrejo, Kecamatan Bumiaji. The program deals with problems related to the cultivation of strawberries, the production of strawberry jelly drinks, and business permits. The activities during the community services were 1) the assistance for strawberry farmers to enhance the cultivation of strawberries; 2) the socialization activities related to product strengthening by packaging technology; and 3) the guidance on obtaining business permits. This community service implemented an integrated approach to enhance the creativity and knowledge of strawberry farmer groups to increase the economic value of processed strawberry products. The community service activities provided strawberry plant seedlings for rejuvenation, enabling partners to independently manage and develop strawberry-picking tourism. During socialization activities, the farmer gains an understanding of the necessary business permits. Any spelling, grammar, and punctuation errors have been corrected. Furthermore, the socialization of packaging helped farmers to improve packaging to enhance product quality.